Religious Education Teacher Efforts to Build and Nurture Children's Morals: A Study of Mental Revolution of Junior High School Students - Endang Pasaribu (AL-ISHLAH: Jurnal Pendidikan, 2023)
Humans possess inherent moral potential prior to birth, which necessitates consistent cultivation via diligent effort and early schooling. The process of developing and applying morals is not immediate; moral education necessitates a significant investment of time, effort, and other interdependent factors to establish and cultivate a sound character framework. Christian Religious Education (PAK) Teachers are educated people with a mission to teach students the truth of God's Word. This study aimed to determine the efforts of Christian religious education teachers in building and nurturing children’s character who can change their minds. Using the library research and case study method, the data sources are PAK teachers and Christian students in this qualitative research method. The results of this study that can be said that Christian religious education teachers who have experienced as agents of transformation took change play a role in shaping the character or moral on children. The formation of student character aims to make students know the truth and errors and the meaning of each action they do. Through correct understanding students were able to make decisions and take responsibility in this modern era.